2014
DOI: 10.1111/ijun.12052
|View full text |Cite
|
Sign up to set email alerts
|

The role of dietary habits in urinary stone disease

Abstract: Urolithiasis is the third most common urinary disease and evidence shows that the incidence of urolithiasis has increased continually during the past decades. The relationship between urinary stones and diet has been known to some extent but there are different opinions about it. This research was done to determine the relationship between dietary habit, food resources intake and urinary stone disease. This is a case-control study on 161 adult patients with urinary stone disease who referred to Hasheminejad Ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 29 publications
(50 reference statements)
0
29
0
Order By: Relevance
“…Non-adherence to treatment regimen has been defined as non-conformity of individuals' behaviors to health or treatment advices. It is a complicated behavioral process, which is affected by various factors, including patients' characteristics, patient-physician relationship, healthcare system [14], and a combination of personal, spiritual, behavioral, and religious beliefs [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Non-adherence to treatment regimen has been defined as non-conformity of individuals' behaviors to health or treatment advices. It is a complicated behavioral process, which is affected by various factors, including patients' characteristics, patient-physician relationship, healthcare system [14], and a combination of personal, spiritual, behavioral, and religious beliefs [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has demonstrated that older women handle these hurdles depending on their social and cultural backgrounds. In other words, each disease is caused, experienced, and managed differently by different people based on the social and cultural backgrounds of the society they live in van den Muijsenbergh and Lagro-Janssen (2006) , Andersson et al (2008) , Hayder and Schnepp (2010) , Gjerde (2012) , Shirazi et al (2014) , Özkan et al (2015) , Heidari et al (2021) , Shakery et al (2021) . Thus, to determine the psychosocial effects of urinary incontinence on older women, their sociocultural backgrounds should be considered ( Sinclair and Ramsay, 2011 ; Laganà et al, 2014 ; Alshammari et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…10 In addition, due to the genetic inheritance of this disease, 11 awareness of patients' first-degree relatives about the diseases and making the necessary changes in lifestyle and behavioural habits could help reduce the risk of the disease among family members. 12 The results of various studies have shown that several factors such as personal characteristics, 13 individual lifestyle habits, 14 physical activity, 15 obesity, 16 body mass index, 17 dietary habits, 18 consuming alcoholic drinks and smoking 1,6 played critical roles in the development of renal stones. Sakhaee et al also reviewed the literature and referred to urolithiasis as a systemic disorder that could be associated with underlying diseases such as coronary artery disease, hypertension, type II diabetes, metabolic syndrome, bone loss, chronic kidney disease and urinary tract infections.…”
Section: Introductionmentioning
confidence: 99%